Cultural Literacy and Youth Character: The Mediating Role of Organizational Participation - Atik Yuliawati; Achmad Supriyanto (Journal of Educational Studies, 2026)
In contemporary education, character development is considered as important as cognitive achievement. Cultural literacy has been widely recognized as a key factor in fostering tolerance, identity, and social awareness. However, its impact often remains limited to classroom settings and does not always translate into real-life behavior. This study aims to examine how cultural literacy influences youth character through the mediating role of organizational participation. This research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 55 members of youth organizations in Malang Regency using a structured questionnaire with a five-point Likert scale. The results reveal that cultural literacy does not have a direct significant effect on youth character. However, it significantly influences organizational participation, which in turn has a strong positive effect on character development. Furthermore, organizational participation fully mediates the relationship between cultural literacy and youth character. These findings suggest that cultural knowledge alone is insufficient to shape character without meaningful social engagement. This study highlights the importance of integrating formal education with real-world social experiences to foster holistic character development.